UNVEILING THE PSYCHOLOGICAL DYNAMICS OF THE MAIN CHARACTER IN “OPPENHEIMER” MOVIE - Fitriyah, Fitriyah; Setiawan, Kevin; Titian Adi, Wiruma (UIN Alauddin Makassar, 2025)
The movie is one of the most popular forms of literary media, and film is a tool that can be used to analyze the psychology of the characters in it. This research aims to analyze the psychological conditions, such as stress and pressure from the World War II situation, and how the responsibility for the development of the atomic bomb can affect Oppenheimer's thoughts, emotions, and decisions. One of the most impactful films on the history of psychology is Oppenheimer, directed by Christopher Nolan, which is known for its intricate storytelling and stunning cinematography. The movie is known for exploring the life and work of J. Robert Oppenheimer, an American physicist who played a pivotal role in the development of the atomic bomb during World War II. The writers used a qualitative descriptive method and Sigmund Freud's theory of psychoanalysis to analyze the psychology of the main character in the film. As a result of this research, the writer found several psychological conditions such as stress/depression, anxiety, resilience, euphoria. Based on several movie scenes, it shows that the psychological factors that influence the actions of the main character are Desire and Moral, these two factors are very influential and contradictory in the actions taken by Oppenheimer throughout the movie.